New species and new distribution records of Lestremiinae, Micromyinae and Porricondylinae (Diptera: Cecidomyiidae) in Sweden - Jaschhof, Mathias; Jaschhof, Catrin (Zootaxa, 2015)
The Swedish species of fungivorous Cecidomyiidae have been the subject of comprehensive inventory in recent years (2004–2012). Notwithstanding these efforts,which are unparalleled in the remainder of Europe and the World, a follow-up project running over four months (May–August, 2014) revealed the presence in Sweden of an additional 28 species of Lestremiinae, Micromyinae and Porricondylinae. These discoveries, comprising 10 species new to science and 18 species new to the Swedish fauna, are outlined and discussed in terms of taxonomic position and geographical distribution. New species are described and named as follows: Aprionus forshagei, Aprionus gustavssoni, Aprionus karlssonorum, Aprionus lindgrenae, Aprionus magnussoni (all in Micromyinae), Asynapta panzari, Asynapta suzzae, Dicerura peterssoni, Monepidosis tinnerti, and Tetraneuromyia wilksae (all in Porricondylinae). Serratyla acuta (Spungis), originally classified as a Porricondyla, is a new combination.